2019
DOI: 10.1021/acssuschemeng.9b02157
|View full text |Cite
|
Sign up to set email alerts
|

More Ca2+, Less Na+: Increase the Desalination Capacity and Performance Stability of NaxCayCoO2

Abstract: Faradaic deionization (FDI) provides an effective solution to respond to the global water crisis. However, the ions intercalation/ deintercalation process with multiple redox reactions leads to structural collapse and unstable cyclability. Here, we develop an asymmetrical FDI device assembled by Ca 2+ -decorated Na x CoO 2 (x ≤ 0.71, y ≤ 0.05) as the Faradaic negative electrode and activated carbon as the positive electrode. Na 0.27 Ca 0.03 CoO 2 •0.6H 2 O was synthesized via a facile sol−gel and chemical oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…To stabilize the structure of NCO is the key point to get a good desalination performance. Zhou et al (2019) [90] synthesized the Na 0.27 Ca 0.03 CoO 2 •0.6H 2 O from Co(NO 3 ) 2 , Ca(NO 3 ) 2 , NaNO 3 and citric acid. Compared to the undoped NCO, the new material got almost the same pair of oxidation/reduction peaks but a higher capacitance of 292 F•g −1 .…”
Section: Sodium Cobalt Oxide and Cobalt Oxidementioning
confidence: 99%
“…To stabilize the structure of NCO is the key point to get a good desalination performance. Zhou et al (2019) [90] synthesized the Na 0.27 Ca 0.03 CoO 2 •0.6H 2 O from Co(NO 3 ) 2 , Ca(NO 3 ) 2 , NaNO 3 and citric acid. Compared to the undoped NCO, the new material got almost the same pair of oxidation/reduction peaks but a higher capacitance of 292 F•g −1 .…”
Section: Sodium Cobalt Oxide and Cobalt Oxidementioning
confidence: 99%
“…For example, doped Zn 2+ ions can improve the electron conductivity, and doped Ca 2+ ions can enhance the capacity. 36,37 However, simultaneously boosting the ion and electron transfer remains a major challenge. In order to enhance the specific capacity and improve the cycling stability of Na x MO 2 , preintercalation of the electrode has been adopted as an effective method to improve the electrochemical performance by introducing the guest species including inorganic ion or organic molecules into the host interlayer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous works have demonstrated that desalination capacity can be enhanced by controlling the sodium content through chemical and electrochemical preactivation. , Our team has proved that a doped heteroatom strategy between the interlayer and slab is an effective way to improve the electrochemical characteristics for CDI application. For example, doped Zn 2+ ions can improve the electron conductivity, and doped Ca 2+ ions can enhance the capacity. , However, simultaneously boosting the ion and electron transfer remains a major challenge. In order to enhance the specific capacity and improve the cycling stability of Na x MO 2 , preintercalation of the electrode has been adopted as an effective method to improve the electrochemical performance by introducing the guest species including inorganic ion or organic molecules into the host interlayer .…”
Section: Introductionmentioning
confidence: 99%
“…Because chloride is the only predominant anion present in the produced water, regulated cations, namely, barium and radium, are soluble and highly mobile. Consequently, they pose long-term health and environmental hazards …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they pose long-term health and environmental hazards. 46 The same Marcellus geographic region in the northeastern United States also has long been confronted with severe acid mine drainage (AMD) problems. AMD is a natural biogeochemically formed water stream primarily from tens of abandoned mines that are acidic and contain significant amounts of sulfate resulting from biological oxidation of sulfide ores.…”
Section: ■ Introductionmentioning
confidence: 99%